Hermeneutic phenomenological approach to the experiences of the individuals living with schizophrenia: A qualitative study - Vadivelan Kanniappan; J R Abishek (Wolters Kluwer Medknow Publications, 2023)
Background: Schizophrenia affects various spheres of life causing so many difficulties and burden, but the studies focusing on the experience of individuals living with schizophrenia with reference to the Tamil Nadu context are sparse. Material and Methods: A qualitative interview based on a hermeneutic phenomenological approach was conducted with 10 individuals living with Schizophrenia and was recorded. The responses were transcribed and coded. Based on codes, domains and subdomains were identified. Results: Six themes were identified, under which the participant's burden was described. Participants expressed a deep longing for love and care. They were deprived of family's affection. Participants felt economically insecured, which was owing to their unemployment. Participants had many physical complaints including sleep disturbance and fatigue. Participants expressed that they had failing memory, concentration issues, and difficulty in planning. Most of the participants felt isolated by family and kin. They did not participate in much social activities due to the fear of judgment and stigmatization. Conclusion: The experience of individuals living with Schizophrenia revealed that they experienced a series of burdens owing to their illness and its impacts that were categorized into various themes including physical, vocational, cognitive, psychological, personal, and social factors.